Concentrations and risks of polychlorinated biphenyls (PCBs) in transformer oils and the environment of a power plant in the Niger Delta, Nigeria. (2019) - Aganbi, Eferhire; Iwegbue, Chukwujindu M.A.; Martincigh, Bice S.
Graphical abstract: Highlights: Soils and water resources around the power plant are contaminated with PCBs. The hepta- and octa-PCB homologues were dominant in the samples. Exposure to PCBs in soils from the power plant could cause human health risk. Abstract: The concentrations of Ʃ14 PCBs were determined, with the aid of gas chromatography-mass spectrometry (GC–MS), in transformer/turbine oils, soils, groundwater, and drainage water collected within a power plant in the Niger Delta of Nigeria. The Ʃ14 PCB concentrations in the transformer oils, drainage water, groundwater and soils ranged from 484 to 48506 mg kg −1, 0.99 to 2.95 mg L −1, 0.16 to 0.56 mg L −1 and from 8.4 to 510 mg kg −1 respectively. The congener distribution patterns in these samples indicate the dominance of highly chlorinated homologues (hepta- and octa-PCBs). The Σ14 PCB concentrations in the transformer oils were above the provisional definition of low persistent organic pollutant (POP) content for PCBs of 50 mg kg −1 as defined in the guidelines on the management of POP waste of the Basel Convention. The concentrations of Ʃ14 PCBs in the soils were above the Dutch guideline value of 1000 μg kg −1 and the estimated incremental lifetime cancer risks relating to exposure of humans to PCBs in soils indicate serious health risks. There is therefore a need to implement a surveillance programme in the vicinity of power plants to determine the impacts on the adjacent ecosystem.